(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This thesis seeks to explore and propose optimized management strategies for pregnant women at risk of miscarriage before 21 weeks of gestation. Miscarriage in the first and second trimesters is a major concern in obstetrics, with significant physical, emotional, and psychological implications for women. The purpose of this study is to review existing clinical evidence and treatment approaches, identify gaps in care, and recommend strategies for more effective management of women at risk for pregnancy loss. The following key areas will be examined: